(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Dr. Shannumukha Sainath A, Assistant Professor, Department of Pharmacy Practice, Nirmala College of Pharmacy (Autonomous), Kadapa, Andhra Pradesh, India Abstract Treatment algorithms for renal disorders are stratified by acuity, etiology, and the pattern of glomerular injury. The management of Chronic Kidney Disease (CKD) is a staged algorithm based on GFR and albuminuria (KDIGO criteria). This pathway focuses on slowing progression via foundational therapies, including aggressive blood pressure control (primarily with RAS blockade), glycemic control (notably with SGLT2 inhibitors), and lifestyle modifications. The algorithm extends to the systematic management of secondary complications, including anemia with iron and erythropoiesis-stimulating agents, and mineral-bone disorder with phosphate binders and vitamin D sterols. In contrast, the Acute Kidney Injury (AKI) algorithm is a diagnostic pathway to rapidly determine and reverse the etiology. It bifurcates into pre-renal (requiring volume resuscitation), intrinsic (supportive care, nephrotoxin removal), and post-renal (urinary decompression). The algorithm for glomerulonephritis (GN) is driven by serology and renal biopsy. Crescentic, rapidly progressive GN (RPGN) necessitates an emergent algorithm of high-dose corticosteroids combined with either cyclophosphamide or rituximab, and plasmapheresis for anti-GBM disease. Nephrotic syndrome management is also etiology-specific based on biopsy, with the algorithm for adult minimal change disease centered on high-dose corticosteroids, while algorithms for focal segmental glomerulosclerosis or membranous nephropathy involve more complex immunosuppressive regimens Keywords: Chronic Kidney Disease, Acute Kidney Injury, Glomerulonephritis, Nephrotic Syndrome, KDIGO, RAS Blockade VIEW PDF